Ethanol extract of Cotinus coggygria leaves accelerates wound healing process in diabetic rats - ŞEN, ALİ; AKAKIN, DİLEK; AKSOY, HALİL; BİTİŞ, LEYLA; SANCAR, MESUT; ŞEKERLER, TURGUT (TAYLOR & FRANCIS LTD, 2016)
Context:Cotinus coggygria Scop. (Anacardiaceae) leaves that were used as wound healing in traditional Balkan and Anatolian folk medicine, could be potentially effective in treating diabetic wounds.Objective: This study investigates biochemical and histological effects of ethanol extract of C. coggygria (CCE) on excision wound model in diabetic rats.Materials and methods: This study was conducted on diabetic Wistar albino rats, which were injected by a single dose (50mg/kg i.p.) streptozotocin. Afterward an excision wound model was created in all animals; diabetic control rats were applied topically simple ointment and diabetic treatment rats were applied topically 5% (w/w) ointment with CC, once a day during the experimental period. Malondialdehyde, glutathione and hydroxyproline levels in wound tissues were investigated at the end of 3rd, 7th, and 14th days. Histopathological examination was also performed.Results: Hydroxyproline content was significantly increased in the CCE treated group versus control after the 3rd and 7th days (15.33 versus 11.83; 19.67 versus 15.67mg/g, p<0.05; respectively). A statistically significant elevation in glutathione at the end of 3rd, 7th, and 14th days (5.13 versus 1.58, p<0.05; 4.72 versus 1.88, p<0.05; 3.83 versus 1.88mol/g, p<0.05, respectively) and a statistically significant decrease in malondialdehyde level at the end of 7th day (4.49 versus 1.48nmol/g, p<0.05) were determined in the treated group versus control group. These results were also supported by histological analyses.Discussion and conclusion: These findings indicate that CCE accelerated the cutaneous wound healing process in diabetic wounds, in confirmation of its traditional use.
Keywords: Anacardiaceae; diabetes; excision wound; hydroxyproline; INJURY; TURKEY; SCOP.